The rise and fall of the energy-carbon Kuznets curve: Evidence from Africa - Olatunji Abdul Shobande; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Purpose - This paper provides an analysis of the energy-carbon Kuznets curve hypothesis (CKC) using a second-generation panel methodology. Design/methodology/approach - Specifically, we investigate whether energy consumption, natural resources, and governance explain the CKC proposition. Our empirical strategy is based on the Westerlund panel cointegration test, augmented mean group (AMG), and vector autoregressive (VAR) panel Granger-causality tests. Findings - The results suggest that the CKC hypothesis is incomplete without these mechanisms, as they play a critical role in reducing carbon emissions in Africa. We recommend improving the environmental standards and proper regulatory and monitoring systems to reduce carbon emissions and promote sustainable development in the continent. Originality/value -The study revisits the CKC hypothesis with particular emphasis on governance and more robust empirical estimation techniques.
Keywords: 330; carbon cuts; Energy consumption; Governance; Climate crisis; Panel analysis; Africa